2016
DOI: 10.1186/s41100-016-0061-z
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for acute kidney injury after initial acute aortic dissection and their effect on long-term mortality

Abstract: Background: Several reports have discussed the risk factors for acute kidney injury (AKI) after thoracic aortic surgery and aortic dissection and the increased mortality in patients with AKI. However, there are few reports on the risk factors for AKI with combined medical and surgical treatment and the influence on mortality. The aim of this study was to clarify the risk factors and long-term effects of AKI on mortality and kidney function after acute aortic dissection in a cohort at our hospital. Methods: We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…A retrospective study by Kato et al showed that TAAD is a risk factors for AKI after aortic dissection, and AKI increased the all-cause mortality. [7] Another study by Pisimisis et al showed that thoracic aortic endograft has a significant rate of renal dysfunction. [8] Some literatures revealed renal ischemia as risk factor of surgical outcome of acute TAAD.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study by Kato et al showed that TAAD is a risk factors for AKI after aortic dissection, and AKI increased the all-cause mortality. [7] Another study by Pisimisis et al showed that thoracic aortic endograft has a significant rate of renal dysfunction. [8] Some literatures revealed renal ischemia as risk factor of surgical outcome of acute TAAD.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, the circuit consists of a membrane oxygenator, a heat exchanger, and two rolling pumps, which can bifurcate the arterial line for both artery perfusion and inferior vena caval perfusion as necessary. For patients in the RIVP group, moderate hypothermia (defined as a nasopharyngeal temperature of [26][27][28] °C and rectal temperature of 28-30 °C) will be induced under CPB, then systemic perfusion will be stopped and the aorta opened. ACP and RIVP will then be performed using the two rolling pumps.…”
Section: Experimental Intervention Protocolmentioning
confidence: 99%
“…2008;23(5): 480-7. ] The current preferred strategy for AAAD surgery is ACP+MHCA at [25][26][27][28][29][30], [endnoteRef:19]. ACP is performed by the perfusion of oxygenated blood via the subclavian artery, innominate artery, or the right axillary artery during hypothermic circulatory arrest (HCA) Since lower-body circulatory arrest is needed during ACP, organs in the lower body such as the viscera and spinal cord are still at risk of ischemia.…”
mentioning
confidence: 99%
“…Nevertheless, ACP + MHCA is associated with overall 30-day mortality rates of 5.3–19% [22, 23] and stroke rates of 6.7–10% [24, 25]. The incidence of acute kidney injury in ACP + MHCA ranges from 19 to 54%, [26, 27] with 5–9% of these patients requiring renal replacement therapy, which is itself associated with an elevated short-term mortality rate of 30–75% [26, 28].…”
Section: Introductionmentioning
confidence: 99%